Association of Rotating Night Shift Work with BMI and Abdominal Obesity among Nurses and Midwives - Peplonska, Beata (PLoS One, 2015)
BACKGROUND: Mounting epidemiological evidence suggests that night shift work may contribute to the etiology of increased body weight. The present study aimed to examine association between rotating night shift work and body mass index (BMI), and abdominal adiposity respectively among nurses and midwives. METHODS: A cross-sectional study was conducted among 724 female nurses and midwives, aged 40-60 years (354 rotating night shift and 370 daytime workers) in Łódź, Poland, between 2008 and 2011. Information about occupational history and potential confounders was collected during personal interviews. Anthropometric measurements of body weight, height, waist (WC) and hip (HC) circumference were made, and body mass index (BMI), waist to hip ratio (WHR) and waist to height ratio (WHtR) were calculated. GLM regression models and multinomial logit regression models were fitted to explore the association between night shift work and anthropometric parameters, with adjustment for age, body silhouette at age 20, current smoking status, packyears, marital status, and menopausal hormone therapy use. RESULTS: Cumulative night shift work showed significant associations with BMI, WC, HC and WHtR, with BMI increasing by 0.477 kg/m(2) per 1000 night duties and by 0.432 kg/m(2) per 10000 night shift hours, WC increasing respectively by 1.089 cm and 0.99 cm, and HC by 0.72 cm and WHtR by 0.007 cm for both metrics. Both current and cumulative night work was associated with obesity (BMI≥30kg/m(2)), with OR=3.9 (95%CI:1.5-9.9), in women reporting eight or more night shifts per month. CONCLUSION: The results of the study support the previously reported relations between night shift work and development of obesity.